PENGARUH LIKUIDITAS, OPERATING CAPACITY DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS DENGAN VARIABEL UKURAN PERUSAHAAN SEBAGAI PEMODERASI (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2015-2017) - Dina Hidayatul; Kennedy Kennedy; Pipin Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this research is so test and analyze the influence liquidity,operating capacity and profitabilityon financial distress with firm size as moderatingvariable. The population in this research is all manufacturing companies listed inIndonesia Stock Exchange at 2015-2017. The sampling method used in this study waspurposive sampling. The sample obtained by 84 companies. Hypothesis in this researchare tested by multiple regression analysis using SPSS 25.The result of this study indicatedthat liquidity affects financial distress with significance 0,012 < 0,05, operating capacityaffects financial distress with significance 0,001 < 0,05, profitability affect financialdistress with significance 0,004 < 0,05, firm size moderates the relationship of liquidityon financial distress with significance 0,000 < 0,05 have an affect on financial distress,firm size do not moderates the relations of operating capacity on financial distress withsignificance 0,201 < 0,05 and firm size do not moderates the relations of profitability onfinancial distress with significance 0,656 < 0,05.Keywords : Liquidity, Operating capacity, Profitabilitas, Financial Distress and Firm Size